Mengkaji Potensi Usaha Kecil dan Menengah (UKM) untuk Pembuatan Kebijakan Anti Kemiskinan di Indonesia - Purwanto, Erwan Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
Small medium enterprises can be used as a strategy to overcome problem of poverty in Indonesia. Howeaer, due to the lack of New Order government intervention and attention to this sector and the New Order regime preferences of big companies, this sector has been under-developed. This article discuses how and what steps government should take in order to maximize the potency of small medium enterprises in Indonesia.